2010
DOI: 10.1063/1.3407514
|View full text |Cite
|
Sign up to set email alerts
|

High-speed all-optical terahertz polarization switching by a transient plasma phase modulator

Abstract: We demonstrate high-speed all-optical polarization switching of broadband terahertz frequency electromagnetic fields with subpicosecond switch-on time. This is achieved through the use of a two-plasma configuration in an orthogonal geometry in which one plasma modulates the relative phase of a two-color optical pump field, enabling rapid terahertz polarization modulation at rates limited by the repetition-rate of the control pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…The polarization of THz emission may rotate due to the relative phase shift between the fundamental and the second harmonic waves caused by the preformed plasma. In the case of Wen et al's experiment [28], actually the main cause of the suppression of the THz emission from the main pulse was the polarization rotation. However, the main part of the response recovers within a very short time (30 ps or so), while we observed only a slow response (≈200 ps).…”
Section: Resultsmentioning
confidence: 93%
“…The polarization of THz emission may rotate due to the relative phase shift between the fundamental and the second harmonic waves caused by the preformed plasma. In the case of Wen et al's experiment [28], actually the main cause of the suppression of the THz emission from the main pulse was the polarization rotation. However, the main part of the response recovers within a very short time (30 ps or so), while we observed only a slow response (≈200 ps).…”
Section: Resultsmentioning
confidence: 93%
“…Xu et al used two single-color pulses, where the THz wave generation mechanism is pondermotive force, and reported the enhancement of THz wave generation. Wen et al reported high-speed THz wave polarization switching using two sets of two-color optical excitation at the fundamental and second harmonic frequency [14]. Effects of the interaction of two laser-induced plasmas were reported by Manceau et al [15].…”
Section: Introductionmentioning
confidence: 96%
“…The THz transmission measurements were performed with a 1 kHz amplified Ti:sapphire femtosecond laser system employing a plasma THz generation scheme and an electrooptic sampling detection scheme. [15][16][17] The optical pump and THz probe beams were collinear at normal incidence. Fig.…”
mentioning
confidence: 99%